Analysis of compliance to integrated tomato production by family farmers of Vilhena, Brazil - de Lima, Valdique Gilberto [UNESP]; da Paz, Diego Oliveira [UNESP]; Ceresini, Paulo Cezar [UNESP]; de Macedo, Marcos Aurélio Anequine; de Monteiro Castilho, Regina Maria [UNESP]; Sant'Ana, Antonio Lázaro [UNESP] (My University, 2021)
Tomato production in Vilhena, Brazil, supplies the local market and school meals provided by the National School Meal Program (PNAE). The integrated tomato production system that reduces the use of pesticides provided improved food security for the local population. Current research characterizes the production system of family tomato farmers, linked to the Association of Small Farmers of the Parecis Plateau (Aprocis) of the municipality of Vilhena RO Brazil, and verifies possible adherence to the parameters of integrated production (IP). The 2018 diagnosis was done by technical visits in the tomato production areas. Twenty-three producers of Aprocis were interviewed by means of a form designed to detect the level of adherence of producers to IP. Descriptive statistics were used for data analysis. Results showed that production systems of the farmers surveyed did not comply with recommended standards of integrated production, although almost half of IP practices are used. The above indicated the potential of this group of family farmers to adopt the system.
Análise da conformidade à produção integrada de tomate por agricultores familiares de Vilhena (RO)
Keywords: Association of small producers; Diagnosis; Diseases and pests; Integrated management